Every vow you break [compact disc, unabridged] : a novel - Swanson, Peter, 1968- (Harper Audio, 2021)
Abigail Baskin never thought she'd fall in love with a millionaire. Then she met Bruce Lamb. He's a good guy, stable, level-headed, and kind. But right before the wedding, Abigail has a moment of uncertainty. The drunken one-night stand from her bachelorette weekend, the sexy guy who wouldn't give her his real name, didn't really mean anything she keeps telling herself. She puts the incident out of her mind, and now believes she wants to be with Bruce for the rest of her life. Then the mysterious stranger suddenly appears, and Abigail's future life and happiness are turned upside down. He insists that their passionate night was the beginning of something much, much more. Something special. Something real, and he's tracked her down to prove it.